Simulation based microstructural optimization of thermo‐mechanically treated steel components. Issue 12 (December 2013) - Stein, T.; Fuss, D.; Grahlmann, P.; Luetje, M.; Brueckner‐Foit, A.; Steinhoff, K.; Weidig, U.
Abstract A simplified approach for the simulation based estimation of the phase distribution in a thermo‐mechanically treated steel component is presented. A key aspect of the approach is the time‐temperature relation for each volume element. Based on a forming simulation with a commercial tool the numerically calculated temperature evolution in the component is analyzed with an in‐house code. The code allows estimating the local phase distribution after the forming process with the help of the continuous‐cooling‐diagram of the material used. A first validation fits well with the existing phase distribution in the component, even though the phase transition in the component is critical in terms of time, deformation and local chemical composition of the material used.